HSPA6 is Correlated With the Malignant Progression and Immune Microenvironment of Gliomas - Zhou, Xiang; Ji, Qiankun; Li, Qin; Wang, Peng; Hu, Guowen; Xiao, Feng; Ye, Minhua; Lin, Li; Luo, Min; Guo, Yun; Wu, Weijun; Huang, Kai; et al. (Frontiers in Cell and Developmental Biology, 2022)
Gliomas are lesions occupying the primary intracranial space occupying lesion and are associated with a high mortality rate. Current treatments for glioma are very limited. Recently, immunotargeted therapy of the glioma microenvironment has been developed. Members of the 70 kDa heat shock protein (HSP70) family are involved in the development of many tumors and immunity. HSPA6 protein belongs to the HSP70 family; however, the biological function of this protein in gliomas has yet to be evaluated. In the present study, a range of analyses, involving protein networks, survival, clinical correlation, and function, revealed that the expression of HSPA6 was negatively correlated with clinical prognosis and closely associated with immunity, invasion, and angiogenesis. Quantitative protein analysis confirmed that HSPA6 was expressed at high levels in patients with glioblastoma. Vitro experiments further verified that HSPA6 enhanced the malignant progression of glioma cells by promoting proliferation, invasion and anti-apoptosis. We also found that HSPA6 was closely correlated with genomic variations and the tumor microenvironment. Collectively, we demonstrated that HSPA6 may represent a new therapeutic target to improve the prognosis of patients with gliomas.